Primary Renal Lymphoma in a Cat - Cássia Gouvêa Félix Dias; Bruno dos Santos Coimbra; Isac Orlando Gasperazzo Bins; Renan Henrique Christ; Lais Batista Vinter; Eduarda Pereira Andrade; Jéssica Miranda Cota; Pereira, Clairton Marcolongo (Acta Scientiae Veterinariae, 2024)
Background: Lymphoma is a hematopoietic tumor characterized by the clonal proliferation of malignant lymphocytes. It is the most frequently observed neoplasm in cats, accounting for approximately 33% of all tumors diagnosed in this species. Primary renal lymphoma accounts for approximately 1.5% of tumors diagnosed in felines and usually affects middle-aged to elderly cats and European breeds. This study describes a case of renal lymphoma in a feline, emphasizing the clinical, laboratory, imaging, and anatomopathological findings of this disease. Case: A 3-year-old spayed mixed breed cat, weighing 3.3 kg, presented apathy, lack of appetite, prostration, polydipsia, restlessness, tremors, sudden incoordination, and increased abdominal volume. Blood counts, serum biochemistry, urinalysis, radiography, and abdominal ultrasonography were performed. Blood count showed leukocytosis, with many atypical lymphocytes and thrombocytopenia. Serum biochemistry revealed azotemia, mild hypokalemia, and low alkaline phosphatase levels. Radiography showed an increase in the kidney dimensions and asymmetry of the kidney silhouettes, indicating a mass effect. Ultrasonography revealed enlarged dimensions, irregular contours, and bilateral nodular features. However, the corticomedullary definition was preserved. Kidney cytology revealed a high number of lymphocytes in smears, with a predominance of medium to large lymphocytes, suggestive of lymphoma. The animal underwent chemotherapy with lomustine, vincristine, prednisolone, and doxorubicin; however, due to the recurrence of clinical signs, the animal died. Macroscopically, the kidneys were enlarged, irregularly contoured, and white in color. When cut, a loss of renal architecture was noted, with blurring of the cortical and medullary regions. Histologically, the renal architecture was obliterated and replaced by a monomorphic population of atypical lymphocytes. The histological diagnosis was compatible with diffuse renal large-cell, high-grade, immunoblastic lymphoma. Immunohistochemistry showed positive immunostaining for CD20 and PAX-5 in the cell cytoplasm and negative immunostaining for CD3. Ki67 was detected in approximately 40% of neoplastic cells. The final diagnosis was primary diffuse large B-cell renal lymphoma. Discussion: The diagnosis of primary renal lymphoma was based on the occurrence of this tumor only in the kidneys of the animal. Renal lymphoma is the most common primary neoplasm affecting cat kidneys. The diagnosis of lymphoma in animals is based on cytological and/or histological examination. In addition, the final classification is performed using immunophenotyping (T and B cells), histology, and/or cytology to evaluate the cellular and nuclear characteristics, histological organization, and growth patterns of the lymphomas. The current clinical signs are related to renal failure, including neurological signs caused by uremia. There is a relationship between the occurrence of lymphoma in felines and retroviral infection; however, it was not possible to test the animal for retroviruses. The alterations observed in hematological examinations are related to the ongoing neoplastic process. The imaging findings in this case were similar to those observed in other studies on renal lymphoma. The treatment used in this study was the L-CHOP protocol, which has been associated with the treatment of different types of lymphomas in several studies on feline lymphomas. The median survival of cats with renal lymphoma is 50 days. In this case, the patient survived 30 days after hospital admission. Keywords: kidney, neoplasm, necrosis, immunohistochemistry.